2015
DOI: 10.1108/jabs-03-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of intellectual capital disclosure: a meta-analysis review

Abstract: Purpose – The study aims to examine the relationship between the corporate disclosure on intellectual capital and five firm characteristics, namely, size, leverage, profitability, age and industry type. Design/methodology/approach – The research uses a meta-analysis technique by taking 19 articles published between 2003 and 2013. Thus, this study integrates and accumulates the findings of prior studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 45 publications
(80 reference statements)
3
27
1
5
Order By: Relevance
“…The control variables used in this study are return on assets (ROA) and leverage. Research conducted by Haji and Ghazali (2013) Eddine et al (2015); Ousama et al (2012) found that profitability has a significant effect on IC disclosure. Whereas Atan & Rahim (2012); Taliyang et al (2011) argued that profitability has no significant effect on IC disclosure.…”
Section: Control Variablesmentioning
confidence: 98%
See 2 more Smart Citations
“…The control variables used in this study are return on assets (ROA) and leverage. Research conducted by Haji and Ghazali (2013) Eddine et al (2015); Ousama et al (2012) found that profitability has a significant effect on IC disclosure. Whereas Atan & Rahim (2012); Taliyang et al (2011) argued that profitability has no significant effect on IC disclosure.…”
Section: Control Variablesmentioning
confidence: 98%
“…In addition to firm size, this study chooses market share to be the second factor that affects the quality of ICD. Eddine et al (2015) found that company size, profitability, and industry type positively affected ICD. Companies with a dominant market share will tend to maximize profits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Audit committees that are qualified, understand and have extensive experience in corporate governance and accounting competencies are assessed to be able to suppress the opportunistic attitude of management in corporate management processes and corporate information disclosure practices. Companies that have a qualified audit committee will be able to pursue extensive and qualified information reporting (Cahya, 2013;Ho et al, 2012;Eddine et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the current research frameworks have started moving towards the matter of human abilities and skills. This means there are various studies of intellectual capital, done either conceptually (Eddine at al., 2015) or empirically.…”
Section: Introductionmentioning
confidence: 99%